Scenarios for Development of Scientific and Innovative Potential of Ukraine under Conditions of a New Industrial Revolution and Association with the EU - Matyushenko Igor Yu. (Problemi Ekonomiki, 2016)
The article presents the results of the scenario simulation of scientific and innovative development of Ukraine to determine the appropriate method of its management under conditions of a new industrial revolution and association with the EU. It is shown that the best scenario that in the long run provides a significant improvement in the results of scientific and technological development is a scenario of increasing the level of R&D expenditures to the EU target figure amounting to 4% of GDP. But this scenario is unlikely. It is found that the optimal level of expenditures can be considered as 2.5% of GDP, which can be achieved in the medium term; in this case raising the level of expenditures to 1.7-2% of GDP gives certain results but does not produce sufficient resources for a long-term development. It is proved that in order to achieve significant results in scientific and technological development, the increase in expenditures on R&D should be accompanied by forming clusters, increasing the level of protection of investors, providing development of high-tech industries and employment in this sphere, as well as facilitating the access to ICTs. It is found that a prerequisite for an effective scientific and technological development is stimulation of the population interest in obtaining high-quality professional education, including through the promotion by employers.